Análisis del proceso logístico de exportación de banano para la asociación de productores bananeros orgánicos Agroverde de la provincia de El Oro - Valencia Valarezo, Pamela Isabel (2015)
This research is based on the logistics of exports, trade policies that exist at the international level, the influence of customs in the logistics and trade; Likewise transportation as the linchpin in international trade is one of the sections of this paper. This project focuses on finding solutions that exist in different companies in the commercial field worldwide, one of the issues the logistics process they made to market your product, since many entrepreneurs feel fatigued by obstacles, requirements, and restrictions at the time of the operation, herein core academic standards required which are scientific articles (papers) that must be related to the problem and give a contribution to its analysis and subsequent solution is found.